33 Commissioning and dosimetric characteristics of new halcyon system. (December 2018) - Bernard, V.; Fafi, S.; Nguyen, D.; Khodri, M.
Abstract : Introduction: A new Halcyon linear accelerator had been installed at clinique Charcot in Sainte-Foy-Lès-Lyon. It's the first one in France. The accelerator head is mounted on a ring gantry. There is no jaws and, for each bank, two MLC (proximal and distal) of 29 and 28 leaves of 1 cm width at isocenter with an offset of 5 mm to minimize the transmission. The maximum speed of the leaves is 5 cm/s. The maximum field size is 28 × 28 cm 2 . Halcyon system has one unique energy of 6XFFF and a maximum dose rate of 800 UM/min. The MV imaging panel size is 43 × 43 cm 2, fxed at a distance source to imager of 154 cm and its resolution is 0.22 mm at isocenter. Currently, Halcyon system has only MV imaging (MV/MV or MV CBCT). Imaging dose is calculated by TPS Eclipse (Varian) and taken into account during optimization. Beam model of Halcyon is already preinstalled and fully modelled in Eclipse. Methods: All the preinstalled data in Eclipse were measured in a water tank Blue Phantom 2 (IBA) using CC13 (IBA), EDGE (SunNuclear) et Farmer (PTW) detectors in accordance with Varian measurements. PDD, profiles, FOC, transmission factor and DLG measurements were compared with preinstalled beam model. Calculated dose distribution with AAA algorithm for PDD and profiles were compared with our measurements using tolerances from SFPM report n°27. End-to-end and RapidArc commissioning were performed. Imaging dose from clinical radiotherapy plans were calculated from several anatomical regions and measured in an anthropomorphic phantom CIRS with a semiflex (PTW) ionisation chamber. Results: A very good superposition of preinstalled data with our measurements was observed for every data. Largest variations were observed for small field profiles 2 × 2 cm 2 . Mean and maximum variations for FOC measurements were −0.03% and 0.71%. Leaf transmission measured through both banks is 0.005%. Beam quality index (PDD(10) with SSD = 100 cm) is 63.5% (Varian specification 63% ± 1). Maximum depth dose for a 10x10cm 2 field size at SSD = 100 cm is 1.28 cm (Varian specification 1.3 cm ± 0.2). For every field sizes 100% of the points for PDD and profiles pass the tolerances from SFPM report n°27. Gantry isocentricity measured with Drum phantom (Varian) is 0.65 mm. Absolute dose difference at isocenter for a VMAT plan measured during an End-to-End test performed in the IMRT Thorax Phantom (CIRS) is 1%. Conclusions: An excellent agreement between Varian preinstalled beam model and our measures were observed and therefore no changes to the preinstalled beam model have been made.